Inhibition of the NAD-Dependent Protein Deacetylase SIRT2 Induces Granulocytic Differentiation in Human Leukemia Cells - Sunami, Yoshitaka (Public Library of Science, 2013)
Sirtuins, NAD-dependent protein deacetylases, play important roles in cellular functions such as metabolism and differentiation. Whether sirtuins function in tumorigenesis is still controversial, but sirtuins are aberrantly expressed in tumors, which may keep cancerous cells undifferentiated. Therefore, we investigated whether the inhibition of sirtuin family proteins induces cellular differentiation in leukemic cells. The sirtuin inhibitors tenovin-6 and BML-266 induce granulocytic differentiation in the acute promyelocytic leukemia (APL) cell line NB4. This differentiation is likely caused by an inhibition of SIRT2 deacetylase activity, judging from the accumulation of acetylated α-tubulin, a major SIRT2 substrate. Unlike the clinically used differentiation inducer all-trans retinoic acid, tenovin-6 shows limited effects on promyelocytic leukemia–retinoic acid receptor α (PML-RAR-α) stability and promyelocytic leukemia nuclear body formation in NB4 cells, suggesting that tenovin-6 does not directly target PML-RAR-α activity. In agreement with this, tenovin-6 induces cellular differentiation in the non-APL cell line HL-60, where PML-RAR-α does not exist. Knocking down SIRT2 by shRNA induces granulocytic differentiation in NB4 cells, which demonstrates that the inhibition of SIRT2 activity is sufficient to induce cell differentiation in NB4 cells. The overexpression of SIRT2 in NB4 cells decreases the level of granulocytic differentiation induced by tenovin-6, which indicates that tenovin-6 induces granulocytic differentiation by inhibiting SIRT2 activity. Taken together, our data suggest that targeting SIRT2 is a viable strategy to induce leukemic cell differentiation.